The Relationship Between Strategic Planning and Organizational Agility in the Indonesian Telecommunication Industry - Ramadhan, Afandi Fajar (Maroon Journal De Management, 2025)
The Indonesian telecommunication industry is undergoing rapid transformation driven by technological advances, regulatory changes, and shifting consumer demands. These dynamics highlight the importance of strategic planning as a foundation for organizational agility, enabling firms to remain competitive and adaptive in a volatile environment. This study aims to examine the relationship between strategic planning and organizational agility in major Indonesian telecommunication companies. A quantitative explanatory design was applied using a survey distributed to 120 managers and decision-makers from four leading providers: Telkomsel, Indosat Ooredoo Hutchison, XL Axiata, and Smartfren. Strategic planning was measured through dimensions of environmental scanning, goal alignment, resource allocation, flexibility in plan adjustment, and performance monitoring, while organizational agility was assessed through responsiveness, decision-making speed, and adaptability. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression, supported by reliability and validity tests. The results show that strategic planning has a strong positive influence on organizational agility, with flexibility in plan adjustment identified as the most significant predictor. The findings suggest that telecommunication firms with stronger planning practices are better able to respond to disruptions, sustain competitiveness, and deliver innovative services. This study concludes that strategic planning is a critical enabler of organizational agility in Indonesia’s digital economy.